Pathways to Energy Savings in Carbon Dioxide Capture,Utilization and Storage Processes - Jinqiang WANG; Baikuan LIU; Xiaoli TIAN; Zhixun LI (Shiyou huagong gaodeng xuexiao xuebao)
Carbon dioxide capture,utilization and storage(CCUS) is a crucial strategy for mitigating the greenhouse effect and reducing CO₂ emissions.As the predominant technology for large⁃scale commercial CO₂ capture,the high energy consumption of the absorption method seriously restricts the popularization and development of CCUS technology.This paper focuses on the energy⁃saving path in the CCUS process,and systematically reviews the latest research progress and achievements in three key directions: The research and development of new absorbents,design of new high⁃efficiency reactors,coupling of CO2 capture and conversion process.The results show that the new absorbent reduces the energy consumption of the absorption reaction process,the high⁃efficiency reactor greatly enhances the mass transfer,and the integrated coupling technology realizes energy saving and consumption reduction from the process source.Future research needs to focus on the verification of the industrial application of new absorbents,the stability and cost control of long⁃term operation of reactors,and the further improvement of the economic efficiency of absorption and conversion integration technology,so as to promote the large⁃scale application of low⁃energy CCUS technology and help achieve the "double carbon" goal.